Einkenni breytingaskeiðs og meðferð þeirra hjá 50 ára íslenskum konum - Bryndís Benediktsdóttir; Kristinn Tómasson; Þórarinn Gíslason (Læknafélag Íslands, Læknafélag Reykjavíkur, 2008)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: The objective of the research was to estimate the prevalence and treatment of climacteric symptoms among 50 years old women, including which doctors are prescribing the hormone replacement treatment (HRT) and what information is given about the risk and benefit of HRT. Material and methods: All (n=956) 50 years old women living in Reykjavík and neighbouring towns were included. A detailed questionnaire was posted to the women with two follow-up reminders. A non-response survey was conducted by phone among those not responding. Results: The response rate was 72.2% (n=690). Sleep disturbances were the most common climacteric complaint occurring every day, mainly difficulty in maintaining sleep (14.8%). Hot flushes occuring every day (3.6%) and every night (2.2%) were more common than palpitations occuring every day (0.5%) and every night (0.2%). One fourth of the women had been to a doctor because of anxiety and 17% because of depression. Women who had been oophorectomised, were suffering from insomnia, hypertension, had high body mass index (BMI) or were not on HRT were more likely to suffer from hot flushes and palpitations. More than every other woman was on HRT (54%). Combination of oestrogen and progesterone were most commonly used. Hot flushes were less common in women on HRT and one third reported better sleep after starting HRT. Women on HRT more frequently visited doctors, were more often suffering from anxiety, chronic tiredness, fibromyalgia and pain. They more often were heavy smokers and had chronic bronchitis. Most often the HRT was started by gynaecologists (67%) but continued by family doctors (56%). About one fifth claimed that they had not received information about the risk and benefit of HRT. Conclusions: More than every other 50 years old woman is on HRT. These women differ in various ways from women not receiving HRT, which underlines the importance of accurate diagnosis and treatment ...